If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 5 = 2x + 5 Reorder the terms: 5 + 15x = 2x + 5 Reorder the terms: 5 + 15x = 5 + 2x Add '-5' to each side of the equation. 5 + -5 + 15x = 5 + -5 + 2x Combine like terms: 5 + -5 = 0 0 + 15x = 5 + -5 + 2x 15x = 5 + -5 + 2x Combine like terms: 5 + -5 = 0 15x = 0 + 2x 15x = 2x Solving 15x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15x + -2x = 2x + -2x Combine like terms: 15x + -2x = 13x 13x = 2x + -2x Combine like terms: 2x + -2x = 0 13x = 0 Divide each side by '13'. x = 0 Simplifying x = 0
| 3.4x+1.2-2.2x-0.5=3.1 | | 4/9x-2=3 | | 2/2y=1/10 | | f(x)=2/3-12 | | T=-3x/y | | 50x-y=-50 | | 2.7x+4.5=12.6 | | 8-6b^2=-2 | | 3(x+9)=x+-15 | | 11x+23=4x-12 | | 1/6=12=21 | | X+3+2(x)+x-5=78 | | (3*y-)/(2-y)=(5-3*y)/(y-2) | | 3(x-5)=3x+9 | | X+3+2(x)-5+x=78 | | -2(-n-2)=12+6n | | 3x-1.5/0.9-1.5x=0 | | f(3)=4x+8 | | 3x+2x+x=4800 | | 22+2x-x=30-4 | | 3x-1.5/0.9-1.5x | | mx^2+2x-1=0 | | 4p-3=6p+13 | | -15-7g=-8g | | sin*4x-cos*4x-1=0 | | 41x-33-25=-145 | | sen*4x-cos*4x-1=0 | | dx=9 | | -q+16=6-2q | | x+4=x*4 | | 8x+7=11x+28 | | 5m^3+8mn-5m^2-8n= |